If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -3) = 4x Reorder the terms: 2(-3 + y) = 4x (-3 * 2 + y * 2) = 4x (-6 + 2y) = 4x Solving -6 + 2y = 4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2y = 6 + 4x Combine like terms: -6 + 6 = 0 0 + 2y = 6 + 4x 2y = 6 + 4x Divide each side by '2'. y = 3 + 2x Simplifying y = 3 + 2x
| -1(8m+4)=4m-2(6m+2) | | -2x+7=2 | | (x^4)-(12x^2)+(11)=0 | | 0.5y+1=4x-2 | | 2x-5y=28 | | -5(x+4)=7-(-5) | | (3+2i)(4+3i)= | | -3x+8=2x+3 | | (3/y)+(2/5)=19/20 | | 6x^2+4x=21 | | -7(2x+8)=14 | | 8z+22=3(3z+11)z | | 11x-3x=400 | | (x^4)-(5x^2)+(4)=0 | | 6(2/3x-7/6)=6*7/2 | | -2y-1=4x+3 | | b+9=24 | | 23x=173 | | 4(x+19)=3x+41 | | y=-4y+1 | | 2(-.26)+7.5=6.2-3(-.26) | | 13x+21=47 | | 3a+7b=1650 | | f(t)=2.25+0.75x | | 4+x=4x-23 | | 0.2c-0.6+.5c=5 | | 3(6+8)=24+18x | | 10m^2-6=404 | | -11.1-2.2x=2.2x/7.7-2x-x^2 | | x^3+5x^2-5x-25=0 | | 1x-2=6x+5 | | (3a+19)+2z= |